Electrical Equivalent Network Modeling of Forearm Tissue Bioimpedance - Fu, Bo; Freeborn, Todd (Proceedings of IEEE Southeastcon, 2019)
In this study, an equivalent electric network utilizing a 2R-1C model as the basic unit is proposed to model the impedance of a biological tissue measured using multiple electrode configurations. The proposed model aims to capture the longitudinal and transverse tissue impedance that also factors in the tissue geometry during parameter selection. Electrical impedance measurements collected from 16 electrode configurations of a human subjects forearm were used as reference values during selection of the equivalent electric network parameters. Comparisons between simulations of the equivalent electric network and bioimpedance measurements support that the proposed network model is able to capture the tissue behaviour and impedance change of the forearm in the longitudinal direction.